Model Pembelajaran Menulis Berbasis Keterampilan Berpikir Tingkat Tinggi (HOTS) di Sekolah Menengah - Anita Candra Dewi (Journal of Humanities, Social Sciences, and Education, 2025)
Writing instruction in secondary schools plays a strategic role in developing students' Higher Order Thinking Skills (HOTS). However, writing instructional practices still tend to focus on linguistic aspects and text structure, thus under-optimally developing analytical, evaluation, and creative skills. This study aims to analyze HOTS-based writing instructional models in secondary schools by reviewing the learning strategies used, the role of teachers as facilitators, the use of technology, and the challenges of their implementation. This study used a literature study approach by reviewing relevant scientific articles, national and international journals, and conference proceedings published in the 2015–2025 period. Data were analyzed using thematic synthesis to identify patterns, best practices, and key obstacles in HOTS-based writing instruction. The study results indicate that the implementation of strategies such as problem-based learning, project-based learning, collaborative writing, and peer review significantly improves students' critical thinking and creativity. Teachers play a crucial role as facilitators, providing guidance, constructive feedback, and mediating critical discussions. Furthermore, the use of digital technology has been shown to support flexibility, collaboration, and effectiveness in the writing process. However, HOTS implementation still faces challenges such as varying student abilities, limited learning time, and teacher preparedness. Therefore, adaptive, contextual learning strategies supported by teacher professional development are needed to ensure optimal and sustainable HOTS-based writing learning.